From past famines to present crises: The epigenetic impact of maternal malnutrition on offspring health in Gaza - Mohamed Adil Shah Khoodoruth (14589828) (2024)
We read with great interest Rajiv Tandon's editorial on mental health amidst wars and violent conflicts, highlighting the severe short- and long-term effects on mental health for affected individuals and their future generations (Tandon, 2023). This paper draws parallels between the nutritional challenges faced by pregnant women in Gaza and historical famines, notably the Dutch Hunger Winter of 1944–1945. The Dutch Hunger Winter provided a unique cohort for studying the long-term effects of prenatal exposure to famine, revealing that the timing of malnutrition during pregnancy significantly impacted birth weights and lifelong health outcomes, including schizophrenia and obesity rates. It was shown that first-trimester exposure to severe famine during the Dutch Hunger Winter was associated with increased risk of schizophrenia in offsprings (Hoek et al., 1998). Moreover, the association between early gestational famine exposure and increased risk of psychiatric disorders like schizophrenia aligns with similar findings from the Chinese Famine of 1959–1961, reinforcing the necessity to address the psychiatric implications of prenatal environmental stressors (Susser et al., 1996, Xu et al., 2009). The timing of the famine was also emphasized in the Dutch famine birth cohort study, which highlighted the significant impact of prenatal malnutrition timing on enduring health outcomes, with late pregnancy malnutrition leading to smaller stature and lower obesity rates, while early pregnancy malnutrition followed by adequate nutrition results in normal birth weights but higher obesity rates in later life (Schulz, 2010). These findings underscore the critical role of early developmental periods in shaping health trajectories and suggest that such prenatal exposures can have heritable, transgenerational effects due to epigenetic mechanisms. Approximately 85% of Gaza's population is displaced, and the entire population of the Gaza Strip (about 2.2 million people) is experiencing acute food insecurity at Crisis level (IPC Phase 3) or worse (The Integrated Food Security Phase Classification (IPC), 2024). This represents the highest proportion of people facing severe food insecurity ever classified by the Integrated Food Security Phase Classification (IPC) initiative for any area or country. Notably, at least one in four households (over half a million people) are facing catastrophic conditions (IPC Phase 5, Catastrophe) according to the IPC. The nutritional impact of famine on pregnant women in the Gaza region presents significant adverse consequences (Elnakib et al., 2024). There is a critical parallel between the nutritional challenges faced by pregnant women in Gaza and the Dutch Hunger Winter of 1944–1945. Prenatal exposure to famine impacts birth weights and lifelong health outcomes and suggests heritable, transgenerational epigenetic effects mediated through mechanisms like DNA methylation (Fig. 1). For instance, famine exposure during the Dutch Hunger Winter's periconceptional period is linked with altered methylation levels in the IGF2 gene, effects that persist across generations (Heijmans et al., 2008). Other Information Published in: Asian Journal of Psychiatry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajp.2024.103999